Revenue management in a refurbishing duopoly with cannibalization - Kurdhi, Nughthoh Arfawi; Dabadghao, Shaunak S.; Fransoo, Jan C. (Journal of Operations Management, 2023)
AbstractRefurbishing has promising economic potential, yet firms remain wary of its potential cannibalization effect on new product sales. Firms need to make strategic choices in competitive settings, involving varying brand strengths and collection constraints. The current study provides an empirical characterization of consumer behavior in such complex settings, which in turn informs an analytical model of optimal pricing policies. The results show that cannibalization (or switching) in a competitive environment has a linear relationship with price discounts, unlike the inverted U‐shaped relationship observed in monopolistic settings. The experimental results also highlight the relevance of cross‐cannibalization, especially for weaker firms (with low brand value) that compete with stronger firms to sell refurbished products. Our subsequent analytical results reveal how both competitors should adjust their refurbished product prices when internal and cross‐cannibalization coefficients change. Weaker firms should focus on surpassing stronger competitors in terms of collection and refurbishing efforts, which implies a predominant focus on operations. Finally, we show that refurbished product prices are a function of, and profits are concave in relation to, the number of core products collected by firms.